Impact of acetylsalicylic acid on primary prevention of cardiovascular diseases: A meta-analysis of randomized trials. (29th August 2020) - Upadhaya, Sunil; Madala, Seetharamprasad; Baniya, Ramkaji; Saginala, Kalyan; Khan, Jahangir
Abstract: Numerous studies have investigated use of acetylsalicylic acid (ASA) for prevention of cardiovascular deaths. The vast majority of the work in this area has focused on secondary prevention. However, underuse of ASA still remains a major issue. Fewer studies have investigated the impact of ASA on primary prevention of cardiovascular death. A meta-analysis of individual participant data from six randomized studies, published in 2009, showed decrease in serious vascular events but at the cost of causing increased bleeding and hemorrhagic stroke. Recent studies have raised a number of key questions regarding the benefits and risks of using ASA for primary prevention.